A TRANSLATIONAL PHASE I STUDY OF TAUROURSODEOXYCHOLIC ACID (TUDCA) TO REDUCE SYMPTOMS AND ER STRESS IN ACTIVE ULCERATIVE COLITIS. (21st January 2021) - Huang, Katherine; Deng, Ruishu; Liu, Ta-Chiang; Gremida, Anas; Deepak, Parakkal; Chen, Chien-Huan; Davidson, Nicholas; Kaufman, Randal; Ciorba, Matthew
Abstract: Background: Emerging evidence has demonstrated that protein misfolding in the endoplasmic reticulum (ER), i.e., ER stress, plays fundamental roles in IBD development in humans. Patients with active Crohn's disease and ulcerative colitis exhibit signs of ER stress in their ileal and/or colonic epithelium. Human genetic studies of IBD have identified primary genetic abnormalities in several genes that encode proteins associated with ER stress. We recently reported that oral delivery of tauroursodeoxycholic acid (TUDCA), a naturally occurring bile salt proven to reduce ER stress both in vitro and in vivo, dramatically decreases the clinical, histological and biochemical signs of inflammation in four different IBD mouse models through reducing ER stress in colonic epithelial cells. Aim: Based on this, our aim was to test the efficacy and safety of TUDCA in an open label, Phase I trial for patients with symptomatic ulcerative colitis. Methods: TUDCA was administered at 2000 mg divided TID for 6 weeks. Baseline and 6 week colonoscopy/flexible sigmoidoscopy with biopsy was performed. Outcome measures include safety, tolerability, Mayo score, and change in markers of ER stress from colon biopsies. Results: To date, complete data is available on 9 of a planned 12 patients. TUDCA was well tolerated and safe with no Grade 3 or greater CTCAE adverse events and no Serious Adverse Events. A significant reduction of 4.6 points on the complete Mayo score was observed from baseline to week 6 (Avg. 8.6 ± 2.5 → 4.00 ± 2.7, P=0.004) with 100% of patients seeing a decrease. Clinical remission, clinical response and mucosal healing were observed in 22%, 67% and 56% respectively. Fecal calprotectin decreased in 67% of patients. As diarrhea can be a side effect of TUDCA treatment at these doses, we also assessed the Partial Mayo Score at two weeks after completion of the trial (8 weeks from baseline). At this time point the Partial Mayo Score significantly decreased by 3.8 points (Avg. 6.2 ± 2.1 → 2.4 ± 1.9, P=0.004) with 67% achieving clinical response and 56% remission. The Robarts Histopathology Index decreased in 8 of 9 patients with a mean reduction of 2.67 points (Avg. 6.4 ± 3.2 → 3.8 ± 2.9, P=0.003). Total serum bile acid profiles changed, but not significantly so, from Wk0 to Wk6. ER stress markers Bip, eIF2a and p-eIF2a were increased in inflamed colon tissue and were lowered post TUDCA treatment in a subset of patients. Conclusions: Preliminary results from a Phase I clinical trial demonstrate that the dietary supplement TUDCA is safe, well tolerated and is associated with significant clinical improvement in a majority of patients with moderate to severely active ulcerative colitis. Mucosal healing and reductions in markers of ER stress were observed in a subset of patients. Study completion and analysis of gene expression and microbiome are underway.